2013
DOI: 10.1039/c3dt00084b
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic ionic liquids from alkyloctamethylferrocenium cations: thermal properties, crystal structures, and magnetic properties

Abstract: Alkyloctamethylferrocenium salts with the Tf2N anion ([Fe(C5Me4C(n)H(2n+1))(C5Me4H)][Tf2N]; Tf2N = bis(trifluoromethanesulfonyl)amide) were prepared, and their ionic liquid properties, thermal properties, crystal structures, and magnetic properties were investigated. The melting points of the Tf2N salts were near room temperature, and decreased with increasing alkyl chain length up to n = 8 and then increased. The salts with PF6 and NO3 anions were also prepared. The melting points of the PF6 salts were higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…[14] We previously found that alkylmetallocenium salts with Tf 2 Ng ave ionic liquids. [15] Therefore, an investigation of the phase transitions in theses alts bridges the gap in the understanding of organometallic ionic plastic crystalsa nd ionic liquids. Plastic phases have also been found in onium salts with the Tf 2 Na nion.…”
Section: Introductionmentioning
confidence: 99%
“…[14] We previously found that alkylmetallocenium salts with Tf 2 Ng ave ionic liquids. [15] Therefore, an investigation of the phase transitions in theses alts bridges the gap in the understanding of organometallic ionic plastic crystalsa nd ionic liquids. Plastic phases have also been found in onium salts with the Tf 2 Na nion.…”
Section: Introductionmentioning
confidence: 99%
“…In [2][PF 6 ] and [3][PF 6 ], these short contacts appear between the ring hydrogens and the fluorine or oxygen atoms (CH arene Á Á ÁF), which are 0.2-0.3 Å shorter than the van der Waals contact distances. 18 6 ] in the high-temperature phase (vide ante), which thermodynamically stabilizes the solid phase. Such cation-anion interatomic contacts often appear in crystals of ionic liquids from sandwich complexes.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Therefore, the effects of molecular structure, such as the length of alkyl substituents, on the physical properties of ionic liquids have been extensively investigated. [17][18][19][20][21] We examine herein how substituent branching and chirality affect the thermal properties of organometallic ionic liquids. [4][5][6][7][8][9][10][11] Although most ionic liquids contain organic cations such as imidazolium cations, various metal-containing ionic liquids that exhibit intriguing functionalities have recently been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Early advances were motivated to develop ILs as green, nonvolatile, nonflammable, and stable solvents, however, recent findings have broadened the field, redefining ILs as low melting salts (melting point <100°C) with an unlimited suite of tunable properties including toxicity, volatility, flammability, and instability . The erstwhile narrow perspective that views ILs as salts of quaternary ammonium, imidazolium, pyrrolidinium, pyridinium, or phosphonium cations has broadened as new cations including the bioinspired cholinium and guanidinium cations as well as metal‐containing cations are paired with various anions to afford salts that meet the definition of IL (Figure ). The evolving complexity of the precursors fosters a conjecture that explains their characteristically low melting point by the structural heterogeneity of a sterically hindered asymmetric cation that impedes strong ionic interaction with the anion as well as precludes ordered packing within a crystal lattice.…”
Section: Introductionmentioning
confidence: 99%